OPTIMIZATION AND IMPLEMENTATION OF MANAGEMENT DECISIONS IN THE DIGITAL ECONOMY BASICS OF ORGANIZATION - Tursunova Sevara Takhirdzhanovna (Scholar Express Journals, 2023)
This article widely covers the scientific and theoretical foundations for the preparation and optimization of management decisions, studies and analyzes the state of preparation and optimization of management decisions at enterprises in the digital economy, and also makes proposals for making and optimizing management decisions. presented
Keywords: Digital economy; optimal management; innovative methods